2015
DOI: 10.13102/sociobiology.v62i3.738
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of Social Wasps (Hymenoptera: Vespidae: Polistinae) in an Agricultural Environment in Bambuí, Minas Gerais, Brazil

Abstract: Studies on the diversity of social wasps in agricultural environments represent an important step to identifying the ideal species to be used in biological pest control programs. There is a growing effort to acknowledge the diversity of such Hymenoptera in the state of Minas Gerais, but information on anthropized environments is still rare. The objective of this study was to obtain data on the diversity of social wasps in the Instituto Federal de Educação, Ciências e Tecnologia de Minas Gerais (IFMG), Bambuí c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0
8

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 37 publications
1
27
0
8
Order By: Relevance
“…The study site is surrounded by pasture and agricultural areas, and thus may act as a refuge, protecting organisms from pesticides (which are used in most of the surrounding areas). According to the Jacques et al (2015) favorable climate conditions in the region may have also contributed to the high observed richness through effects on foraging activity, as demonstrated in several previous studies (Giannotti et al, 1995;Elpino-Campos et al, 2007;Auad et al, 2010). Higher temperature and precipitation, in particular, may have influenced the observed species richness, as there is greater variation in these factors in Cerrado than in forest areas.…”
Section: Resultssupporting
confidence: 52%
“…The study site is surrounded by pasture and agricultural areas, and thus may act as a refuge, protecting organisms from pesticides (which are used in most of the surrounding areas). According to the Jacques et al (2015) favorable climate conditions in the region may have also contributed to the high observed richness through effects on foraging activity, as demonstrated in several previous studies (Giannotti et al, 1995;Elpino-Campos et al, 2007;Auad et al, 2010). Higher temperature and precipitation, in particular, may have influenced the observed species richness, as there is greater variation in these factors in Cerrado than in forest areas.…”
Section: Resultssupporting
confidence: 52%
“…A total of 175 ha are used for agricultural crops (corn, beans, sugarcane, orange, banana, coffee and vegetables) and pastures, and 34 ha are occupied by buildings, most of them are close to the cultivars. The campus has a high diversity of social wasps, with 29 species and 8 genera (Jacques et al, 2015).…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, this research recorded the foraging behavior only in kale, and this species may be foraging in another plant species. This species preys We recorded 4 species, M. labiatus, P. ferreri, P. fastidiosuscula and P. sylveirae that had not been collected previously at the IFMG -Bambuí Campus according to a diversity survey of social wasps previously performed by Jacques et al (2015).…”
Section: Mean Abundance Of Protonectarina Sylveiraementioning
confidence: 99%
“…In 1978, Richards publishes the book "The Social Wasps of the Americas, Excluding the Vespinae", which comprehends an extensive review on the neotropical species, with details on their distribution, morphology and biology; this publication instantly became a milestone for posterior studies on the group, and references to it can still be found in recent publications (e.g. Melo et al, 2015;Jacques et al, 2015).…”
mentioning
confidence: 99%